Localized Development and Application of Controller for Wind Turbines - YE Wei; YU Yong; LI Jun; YAN Zhi (Kongzhi Yu Xinxi Jishu)
In order to get rid of technical barriers, ensure the safety of industrial control and realize the controllability of information security, it is necessary to focuses on the localized development and replacement application of controllers for wind turbine generators (WTG). Emphasizing practicality, integrity, real-time performance, reliability, stability, security and progressiveness, this study prioritized the adoption of the domestic Godson 2K1500 chip and real-time embedded operating system in the localized design and development of controllers to enhance safety, controllability and efficiency. The domestically developed controller was further configured with hardware and I/O point table aligned with the functional requirements of the WTG control system. Furthermore, the study analyzed the communication modes between the controller and interface devices, in addition to outlining a design for software control logic. The designed controller was subsequently incorporated into a WTG, which was put into trial operation for 240 hours after successful commissioning. During this acceptance testing, the system operated stably and reliably, with all performance indicators remaining compliant with national or industry standards. The control system for MW level WTGs based on the domestic controller featuring autonomous controllability was proven to be autonomously controllable, safe and reliable.